Variation of Anxiety and Depression During a 3-Year Period as Well as Their Risk Factors and Prognostic Value in Postoperative Bladder Cancer Patients - Guo, Meiling; Li, Yanjie; Wang, Wentao; Kang, Xu; Chen, Guiyun (Frontiers in Surgery, 2022)
Background: Anxiety and depression are common-recognized and prognostically relevant in cancer patients. The aim of this study was to explore the 3-year longitudinal changes in anxiety and depression, their risk factors, and prognostic value in patients with bladder cancer. Methods: Hospital Anxiety and Depression Scale for anxiety (HADS-A) and depression (HADS-D) scores of 120 postoperative bladder cancer patients and 100 healthy controls (HCs) were assessed. Additionally, the HADS-A and HADS-D scores of bladder cancer patients were also determined at 1 year, 2 years, and 3 years post-surgery. Results: HADS-A score (7.7±3.0 vs. 4.8±2.6), anxiety rate (38.3% vs. 9.0%), HADS-D score (7.7±3.3 vs. 4.3±2.6), depression rate (40.0% vs. 11.0%), as well as anxiety degree and depression degree were all increased in bladder cancer patients compared with HCs (all P<0.001). Besides, the HADS-A score gradually increased from baseline to 3 years (P=0.004), while anxiety rate, HADS-D score, and depression rate did not change significantly (all P>0.050). Gender, tumor size, marriage status, hypertension, diversity, and lymph node (LN) metastasis were associated with anxiety or depression in patients with bladder cancer (all P<0.050). Anxiety was associated with shortened overall survival (OS) (P=0.024) but did not link with disease-free survival (DFS) (P=0.201); depression was not correlated with either DFS or OS (both P>0.050). Conclusion: The prevalence and severity of anxiety and depression are high in patients with bladder cancer, which are influenced by gender, tumor features, marriage status, and hypertension; in addition, their correlation with survival is relatively weak.